WOMEN AND ACCESSORIES: BUSINESS OPPORTUNITY AND CRAFT INDUSTRY - Arsa, I Ketut Sida (E-Journal of Cultural Studies, 2015)
This study is intended to describe the current life style of women which contributes to the development of craft industry, especially the industry of accessories in Bali. In this case, women are used as the subject made use of by the capitalist, that is, the producer of accessories used as the object. The data on the relationship between the craft industrial element, especially the industry of accessories, with the life style of women were obtained using observation and in-depth interview techniques.  The theory of consumerism developed by Jean Baudrillard was used to analyze the field data. The result of the study showed that the stylish performance had caused women to be consumptive. In this case, women had been the most potential target of the market share; therefore, the capitalist perpetually developed new mode or trend. In this way, women were made to follow the newest trend, meaning that their desire had been inspired by various trends which had been developed by the accessory business persons from time to time. Such a phenomenon could be clearly seen when the discourse of “Ajeg Bali” was made to be popular, and when the civil servants, private employees and students were obliged to wear the Balinese traditional dress. Accessories were attached to the woman’s blouse to make it more interesting. It seemed that dress and accessories could not be separated from one another to make performance more perfect. Such a phenomenon contributed to the garment industry and craft industry in order to meet what is desired by the Balinese women.